A Preliminary Investigation of the Behaviour of Rusty Spotted Cats Prionailurus Rubiginosus in Captivity - Jayaratne, C.; Perera, P.K.P.; Dayawansa, P.N. (WILDLANKA, 2015)
Attached
Keywords: Rusty-Spotted Cat; Behaviour; Captivity; Ethogram; Camera trapping; National Zoo Sri Lanka